Sharia Financial for Market Management Apps in the Money Market - Simon Grima; Firdauska Darya Satria; Joko Purwanto; Diyah Anggraeni (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
The industrial revolution 4.0 facilitates people to access all information with smartphones connected to the internet. This is an opportunity for the Islamic finance industry to innovate digitally. There are various sharia financial apps technology that has been registered to OJK, but there should be necessary to adjusted application features with the concept of maqashid sharia (Dharuriyyah, Hajiyat and Tahsiniyat) and analyze the implications of digital applications on sharia financial literacy and inclusion. The division of the dharuriyyah is categorized into 5 basic namely 1) Religion, 2) Soul, 3) Descendants,4) Intellect and 5) Assets. The results of the study indicate that the digital innovation of